1991
DOI: 10.1111/j.1467-6494.1991.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Altruistic Personality from Data on Accident Research

Abstract: The aim of this study was to test whether the concept of an altruistic personality was valid for first aiders who intervened to help the victims of a traffic accident. We derived a number of relevant personality variables that should be related to the willingness to administer first aid. These include locus of control, social responsibility, belief in a just world, empathy, and instrumentality. We obtained data from proven first aiders who had intervened after a traffic accident. Thirty-four of these first aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
2
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(98 citation statements)
references
References 51 publications
2
87
2
7
Order By: Relevance
“…Although there is considerable evidence for the prosocial personality (e.g., Bierhoff et al, 1991;Eisenberg et al, 2002;Penner & Finkelstein, 1998;Staub, 1974), there have been relatively few analyses of the motivational underpinnings of this trait. We have proposed that different motivations underlie the prosocial personality and that these different motivations, in turn, are associated with different personality variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is considerable evidence for the prosocial personality (e.g., Bierhoff et al, 1991;Eisenberg et al, 2002;Penner & Finkelstein, 1998;Staub, 1974), there have been relatively few analyses of the motivational underpinnings of this trait. We have proposed that different motivations underlie the prosocial personality and that these different motivations, in turn, are associated with different personality variables.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the motivation to help others in order to gain pleasure can be contrasted with the motivation to fulfill a duty or conform to a social norm-what we call ''pressure based prosocial motivation''. For example, Campbell (1975) argues that helping behavior is motivated by pressure from cultural institutions, Rosenhan (1970) proposed a concept called ''normative altruism '', and Bierhoff et al (1991) found that people who help in the event of an accident possess a profound sense of duty.…”
Section: Pleasure and Pressure Based Prosocial Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Akékoľvek kvantifikovanie výchovného potenciálu určitého programu alebo intervencie je teda nutne ohraničené konkrétnymi podmienkami, v ktorých sa realizuje, najmä osobnosťou vychovávateľa (Podmanický & Szeliga, 2009) a žiaka (Bierhoff, Klein, & Kramp, 1991;Bierhoff & Rohmann, 2004;Oliner & Oliner, 1988;Penner, Fritzsche, Craiger, & Freifeld, 1995 a i. ), ale aj množ-stvom mnohých ďalších premenných, vrátane kultúry prostredia (Barr & Higginsová, 2007).…”
Section: Etická Výchova a Výskum Prosociálneho Správaniaunclassified
“…Locus of control (LOC) is the degree to which a person believes that their behavior is internally motivated or controlled, contingent on their own actions or personal characteristics, versus external, beyond their control and a function of chance or the control of powerful others (e.g., [20]). Bierhoff et al [10] find that people who are more likely to be altruistic have higher levels of internal LOC, while Singhapakdi and Vitell [72] find that high levels of internal LOC indicate increased moral identity. Cleveland et al [20] find that an internal environmental LOC relates to recycling levels, while an external environmental LOC relates to exoneration of humans from responsibility for sustainability.…”
Section: Consumer Characteristics and Their Response To Carbon Footprmentioning
confidence: 99%